Problem-Solving Skills in Trigonometry as Influenced by Emotional Intelligence and Mathematics Self-Efficacy - Jasmin Joyce C. Valer; Mariel L. Alpas; Ronique Byrlle B. Gaborne; Jobelyn C. Macangga; Abdul J. Jamara (Goodwood Publishing, 2026)
Purpose: This study aimed to determine whether emotional intelligence and mathematics self-efficacy significantly influence the trigonometry problem-solving skills of first- and second-year Bachelor of Secondary Education major in Mathematics students at Davao del Norte State College. Methodology: A descriptive correlational research design was used. A total of 120 students were randomly selected as the respondents. Data were gathered using adapted questionnaires for emotional intelligence and mathematics self-efficacy, along with a researcher-developed test for trigonometry problem-solving skills. Mean, standard deviation, and Spearman’s rho correlation were used for data analysis. Results: The findings revealed that the students demonstrated high levels of emotional intelligence (M = 4.03, SD = 0.46) and mathematics self-efficacy (M = 3.58, SD = 0.52). Their problem-solving performance was also relatively high (M = 35.4, SD = 4.78). However, no significant relationship was found between emotional intelligence and problem-solving skills (r = –0.002, p = 0.979) or between mathematics self-efficacy and problem-solving skills (r = 0.047, p = 0.609). Conclusions: Emotional intelligence and mathematics self-efficacy were not significant predictors of trigonometry problem-solving performance. The findings suggest that cognitive and instructional factors may play a more critical role in students’ mathematical performance. Limitations: The study was limited to first- and second-year mathematics education students from a single institution, used self-reported questionnaires, and a researcher-developed trigonometry test with few items, focusing only on affective variables. Contributions: The study provides evidence that emotional intelligence and mathematics self-efficacy minimally predict trigonometry problem-solving, highlighting the importance of cognitive and instructional factors, and offering guidance for future research and teaching interventions.